APPLICATION OF CONDENSATION EFFECT FOR DUST SUPPRESSION - L. E. Rovin; O. V. Gerasimova (Литьë и металлургия, 2006)
It is shown that using of gases against dust will allow not only to catch fine fi-actions of dust and to reduce the cost for clearance as well.